Postscript: Parallel Distributed Processing in Localist Models Without Thresholds. - Plaut, David C.; McClelland, James L. (Psychological Review, 2010)
A commentary on an article by Jeffrey S. Bowers that appeared in this issue on pp. 300–306. In his article, Bowers contended that grandmother cells in neuroscience are the equivalent of localist representations in psychology, and in that, grandmother cells are biologically plausible. Bowers also argues that neuropsychology is shown to be inconsistent with the distributed representations learned in parallel distributed processing (PDP) models. The writers argue that Bowers' attempt to distinguish between what a neuron responds to and what it codes for, undermines the localist argument he has put forward. They suggest that the PDP approach is grounded in the belief that certain computational principles of neural systems are fundamental to explaining human cognitive performance.